ANALISA PROTEKSI DIFFERENSIAL PADA GENERATOR DI PLTU SURALAYA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Power plants produce electrical energy that will be distributed to consumers. Hence, the power plant is expected to be in a condition which means it can reliably provide electricity continuously with good quality. So as to improve the reliability and continuity of service, the operation of power systems require a safety equipment or protection system to prevent disturbances that disrupt the system. Protection system is an important component to maintain the continuity and reliability of the distribution of electrical energy. Protection system serves to protect equipment from damage in the event of disturbances and minimize disruptions from spreading. With good protection system, the unwanted loss can be avoided, especially in the vital equipment such as generators and transformers. One of the equipment that plays a role in the protection system is a differential protection relays are used to protect generators and transformers. This relay protects the generator and transformer from internal disturbances such short circuit between phases or short circuit of phase to ground. This rele works based on the current setting and operating time has been determined so that it can work quickly and precisely targeted.